A Review of Global Policy Mechanisms Designed for Tropical Forests Conservation and Climate Risks Management - Muthee, Kennedy; Duguma, Lalisa; Wainaina, Priscilla; Minang, Peter; Nzyoka, Judith (Frontiers in Forests and Global Change, 2022)
Deforestation and forest degradation of tropical forests are major global concerns due to their ecological, social, and economic roles. In the wake of climate change and its diverse global effects, fragmentation and degradation of tropical forests have jeopardized their ability to support livelihoods and regenerate climate regulating services. Concerted efforts by local, national, and international players, which are primarily scientific, technological, or economic, have borne minimal results in safeguarding these forests from destruction, necessitating a more integrated and inclusive approach. The Rio Earth Summit (1992) brought together world leaders to set targets and priorities on the global sustainability agenda and laid a strong foundation for international policy cooperation in the future. This study employed a systematic review of articles published between 1992 and 2020 to establish how various policy mechanisms have been developed and evolved to bridge forests and climate change discourse in tropical forests while highlighting their strengths and weaknesses. The initial search of peer-reviewed publications and gray literature yielded 2622 records, which were subjected to inclusion and exclusion criteria based on The Preferred Reporting Items for Systematic Review and Meta Analyses guidelines, resulting in a final list of 65 records for in-depth qualitative analysis. The study establishes that the mechanisms in place have contributed mainly to more coordination and incentives to manage climate risks, primarily through tropical forests conservation. However, hurdles such as inadequate participation and involvement of the local and indigenous people, insufficient national and local policy frameworks and bureaucracies around emissions monitoring, measuring, reporting, and verification processes continue to slow tropical forest conservation. Thus, there is a need for more integrated, multilevel, and diverse stakeholder engagement to achieve the set global targets effectively.